Miss Nelson is missing! - Allard, Harry, 1928-2017.; Marshall, James, 1942-1992. (Boston : Houghton Mifflin, 1977)
The kids in Room 207 take advantage of their teacher's good nature until she disappears and they are faced with a vile substitute.
Keywords: Schools -- Fiction; Behavior -- Fiction